Respostas
respondido por:
0
a) ∆ = b² - 4ac
∆ = 16 - 4 × 1 × 0
∆ = 16
Xv = -b / 2a
Xv = 4 / 2 × 1
Xv = 4 / 2
Xv = 2
Yv = -∆ / 4a
Yv = -16 / 4 × 1
Yv = -16 / 4
Yv = -4
b) ∆ = 0 - 4 × 2 × (-128)
∆ = 512
Xv = 0 / 2 × 2
Xv = 0 / 4
Xv = 0
Yv = -512 / 4 × 2
Yv = -512 / 8
Yv = -64
a) (2,-4)
b) (0,-64)
Espero ter ajudado!!!
∆ = 16 - 4 × 1 × 0
∆ = 16
Xv = -b / 2a
Xv = 4 / 2 × 1
Xv = 4 / 2
Xv = 2
Yv = -∆ / 4a
Yv = -16 / 4 × 1
Yv = -16 / 4
Yv = -4
b) ∆ = 0 - 4 × 2 × (-128)
∆ = 512
Xv = 0 / 2 × 2
Xv = 0 / 4
Xv = 0
Yv = -512 / 4 × 2
Yv = -512 / 8
Yv = -64
a) (2,-4)
b) (0,-64)
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás